2020
DOI: 10.1177/1464420720948541
|View full text |Cite
|
Sign up to set email alerts
|

Influence of multiple scan fields on the processing of 316L stainless steel using laser powder bed fusion

Abstract: The sharp growth that additive manufacturing has been showing recently has broadened its application field and resulted in more varied demand of high-volume parts as well as a general increase in part series. The current focus on productivity enhancement of additive manufacturing has imposed the implementation of multiple-laser systems with larger scan fields. Its usage, combined with adequate layer thickness and laser power selection, makes high-volume parts less challenging to obtain. This paper focuses on u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…A lower repeatability within the AMed samples is observed. This may be explained by the existence of internal defects in the AMed steels, which can compromise their mechanical behaviour, especially their ductility [40,41]. It is also important to consider the relative size effect of those defects when analysing small material samples, as might have been the case for the tested tensile geometries.…”
Section: Resultsmentioning
confidence: 99%
“…A lower repeatability within the AMed samples is observed. This may be explained by the existence of internal defects in the AMed steels, which can compromise their mechanical behaviour, especially their ductility [40,41]. It is also important to consider the relative size effect of those defects when analysing small material samples, as might have been the case for the tested tensile geometries.…”
Section: Resultsmentioning
confidence: 99%
“…Prediction of the mechanical behaviour of additively manufactured alloys under different loading conditions is a substantial step to optimise their performance in complex service environments. 26 Axisymmetric and 3D models were used for the samples under uniaxial tension and compression tests. Axisymmetric CAX4R and C3D8R elements in 3D FEM analysis were used for this study.…”
Section: Fem Simulation Of Tension and Compression Testsmentioning
confidence: 99%
“…For example, Marbury et al [12] reported tool breakage when applying standard cutting parameters thought for conventionally manufactured (CMed) 316 L stainless steel, on the AMed counterpart. On the same alloy, Leça et al [13] have shown that porosity directly influences the cutting loads and reported a relationship between chip segmentation and relative density. Focusing on the effect of cutting velocity, Bai et al [14] have compared the machinability of the AMed A131 steel with its conventional counterpart, focusing on the effect of cutting speed.…”
Section: Introductionmentioning
confidence: 98%